PROBLEMATIKA PEMBENTUKAN REGULASI PEMILU DALAM MEWUJUDKAN PEMILU SERENTAK YANG DEMOKRATIS - Helen, Zennis (Ensiklopedia Sosial Review, 2020)
Election is a means of exercising people's sovereignty. Election regulations continue to change every time an election is held. So that there is no permanent and long-term election regulation. The 2019 simultaneous elections which were regulated by Law No.7 of 2017 concerning General Elections would not last for a period of five years. This is because the DPR and the President are currently forming a new Election Bill which is being discussed between Commission II of the DPR and the government. In Law No.7 of 2017 concerning General Elections, several laws have been codified, namely the Law on Election Implementation, the Law on Legislative Elections, and the Law on Presidential and Vice-Presidential Elections, several separate laws then become one in Law No.7 of the year. 2017 concerning General Election. This is what is called the codification of elections, namely the compliance of laws and regulations relating to elections. When the formation of the Election Bill, there was also a very sharp intersection of interests between political parties, especially those discussing the parliamentary threshold, the electoral system, the threshold for presidential and vice presidential candidates. Because the Election Law is drafted within a period of five years, ideally the Election Law contains very technical and very detailed matters. It is intended that election regulations in the form of regulations at the General Election Commission (KPU) level and Election Supervisory Body Regulations (Bawaslu) can be reduced because at the level of the Law itself, technical regulations are already regulated. This is because too many regulations at the PKPU and Perbawaslu levels will make it difficult for election organizers in provinces, districts / cities, especially when PKPU tends to undergo changes because they have to consult with the DPR. This does not mean that PKPU and Perbawaslu are unnecessary but reduced so that election regulations are not obese. And the enforcement of election law, both administrative disputes, process and criminal law enforcement, must contain the principle of equality of the parties to the dispute. It is prohibited to enforce one-sided election law, selective cutting and so on.